Water consumption habits of a north-western Turkish community: a cross-sectional study. (9th August 2022) - Ayranci, Unal; Yildiz, Merve Sezer; Demirci, Ahmet
Abstract: The aim was to determine the drinking water preferences of people applied to a family health center. This cross-sectional study was carried out from 1 April to 31 May 2022. The data were evaluated using the chi-square test and percent ratios with a significance of p < 0.05. The mean age of all 432 respondents was 48.03 ± 15.86. It was determined that those aged 31–45 had drunk more bottled water ( p < 0.01) and more spring water ( p < 0.001), than those aged 65 and above and had more purified water ( p < 0.001), than women who had more tap water ( p < 0.001), than married people who had more demijohn and tap water ( p < 0.001, each one), than divorced/widows who had more packaged and purified water ( p < 0.001, each one), than the illiterate/literate who had bottled water ( p < 0.001, per one) and than those who had no income/people who lived on the state or municipal assistance who had only carboy water ( p < 0.001). This study suggests that the biggest factor that positively affected the drinking water preference was the packaging of the water. However, the drinking rates of mains water and spring water were quite low. Convincing the authorities to make the mains water drinkable is of great importance in terms of overcoming the public's distrust of mains water. HIGHLIGHTS: This study aimed to close the gap in the studies related to water. People had to use the water options available to them. The biggest factor that positively affected the drinking water preference was the packaging of the water. Convincing the authorities to make the mains water drinkable is of great importance. The only way to prevent environmental pollution caused by packaging water is to switch to mains water. Graphical Abstract